Determinants of drought effects on crown condition and their relationship with depletion of carbon reserves in a Mediterranean holm oak forest - Galiano, Lucía; Martínez-Vilalta, Jordi; Sabaté, Santi; Lloret, Francisco (Tree Physiology, 2012)
Severe droughts may increase physiological stress on long-lived woody vegetation, occasionally leading to rapid defoliation and progressive increase in mortality of overstorey trees. Over the last few years, episodes of drought-induced tree dieback have been documented in a variety of woodlands and forests around the world. However, the factors determining tree survival and subsequent recovery are still poorly understood, especially in resprouter species. We have studied the effects of a single drought episode on crown condition in a holm oak (Quercus ilex L.) forest located in NE Spain 7 years after the drought event. Generalized linear models were used to study the environmental correlates of forest crown condition 7 years after the drought event. Additionally, we evaluated the association between crown condition and the carbon and nutrient reserves stored in lignotubers 7 years after the drought. Our study reveals the multifactor nature of a drought-driven forest dieback in which soil depth and the characteristics of individual trees, particularly their number of stems, determined a complex spatial pattern of tree-level responses. This dieback was associated with a depletion of the carbon reserves in lignotubers 7 years after the episode, representing a reduction of up to 60% in highly drought-damaged trees. Interestingly, in the absence of new acute droughts, successive surveys in 2007–11 showed a direct association between carbon reserves depletion and further deterioration of crown condition. More frequent droughts, as predicted by climate change projections, may lead to a progressive depletion of carbon reserves and to a loss of resilience in Mediterranean resprouter species.
10.1093/treephys/tps02510.1093/treephys/tps025
Keywords: carbon reserves; crown condition; drought resilience; resprouter; tree dieback